Analisis Pengaruh Total Quality Management (TQM) Terhadap Kinerja Organisasi Dengan Pengendalian Internal Sebagai Variabel Intervening (Studi Empiris Anggota Puskopsyah BMT Jawa Tengah) - Retnowati, Eka; Raharja, Raharja (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This research is generally aimed empirically in testing the implementation of total quality management (TQM) on organizational performance by applying the implementation of internal control structure as intervening variable. In the implementation of total quality management (TQM) on Baitul Maal Wa Tamwil is associated with the internal control structure of Baitul Maal Wa Tamwil Puskopsyah member of the performance.Â This research uses quantitative method by using Structural Equation Model (SEM) based on Partial Least Square (PLS) 3.0 component. In the research object, all Baitul Maal Tamwil were selected as the population while the sample in this study focused on members of Puskopsyah (Pusat Koperasi Syariah) BMT (Baitul Maal Wa Tamwil) Central Java, which sampling based on purposive sampling method with total sample there are 97 respondents. The results of this study indicate that the implementation of total quality management (TQM) does not directly affect the performance of the organization but has an effect on the implementation of internal control structure which is the mediator of the relationship between total quality management (TQM) and organizational performance.